Faith, hoe and Money: the social genesis of solidarity-based rural credit cooperatives in Minas Gerais – Brazil (Research, Society and Development, 2021)
This research is part of a new research and discussion agenda on solidarity rural credit cooperatives, which seeks to reveal the structuring, organization and impact of the insertion of a new cooperative system in the state of minas gerais, brazil. Within this perspective, the general objective of this research is to analyze, from an institutionalist perspective, the institutional origins of solidarity credit cooperatives in minas gerais from a case study and qualitative and descriptive research method. The inflections in the trajectory of the organizations that give rise to solidarity credit cooperatives in minas gerais were not promoted only as a rational strategy to increase financial performance, and an institutional dimension covered this process, conditioned by symbolic, political and faith relations. In this scenario, this organizational model emerges from relationships linked to faith (church), hoe (unions) and money (access to financial services).